Enjoyable econometrics - Franses, Philip Hans, 1963- (Cambridge : Cambridge University Press, 2018)
Econometrics can at first appear a highly technical subject, but it can also equip the practitioner with a useful skillset of smart ways to formulate research questions and collect data. Enjoyable Econometrics applies econometric methods to a variety of unusual and engaging research questions, often beyond the realm of economics, demonstrating the great potential of using such methods to understand a wide range of phenomena. Unlike the typical textbook approach, Enjoyable Econometrics follows in the footsteps of Freakonomics by posing interesting questions first before introducing the methodology to find the answers. Therefore, rather than equation-heavy sections based around complex methodologies, the reader is presented with chapters on 'Money' and 'Fashion, Art and Music'. Franses writes in a way that will enthuse and motivate the economics student embarking upon the essential study of econometrics. Indeed, the book shows that econometric methods can be applied to almost anything.
Machine generated contents note: 1. Introduction; 2. Correlation and regression; 3. Money; 4. Financial literacy and numeracy; 5. Postage stamps and banknotes; 6. Fashion, art and music; 7. Academic publications; 8. Trends and fads; 9. The takeaways; Notes, Index.
Title from publisher's bibliographic system (viewed on 20 Jun 2018).
Keywords: Econometrics; Econometrics -- Popular works